Effectiveness of strategic environmental assessment in promoting sustainable development in Tanzania - Emanoel Alfred; Joseph Qamara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper examines the extent to which strategic environmental assessment (SEA) is implemented in Tanzania and whether its implementation is in line with generally practised procedures/criteria. Out of 17 completed SEA, eight cases were purposively selected and assessed by applying an analytical framework that incorporates commonly accepted SEA criteria, which require SEA to be integrated, sustainability-led, stakeholder-driven, inclusive, as well as accountable and transparent. The study finds that the SEAs are not completely consistent or inconsistent with any of the five ideal criteria. Instead, there is a mix of consistency among the sub-criteria. Some of the sub-criteria such as institutional integration mechanisms, dissemination of SEA results, as well as enforcement mechanisms for compliance are yet to be considered in Tanzanian SEA practice. In addition, the findings indicate that there are limited linkages between the policies, plans, and programmes (PPPs) formulation and SEA processes. The SEA tends to enter the planning process late, thus limiting their ability to influence sustainability outcome of the proposed PPPs. It is critical also to find that bills, regulations, and strategies are not yet subjected to SEA processes. The study recommends key interventions to improve Tanzania's SEA practice. These include the establishment of enforcement mechanisms for conducting SEA through performance audit; introduction of registered SEA experts with practicing SEA certificates; responsible authorities to allocate funds for undertaking SEA; as well as conducting awareness and education programmes to the responsible authorities and experts to review, monitor, and conduct SEA effectively. SEA is still evolving in Tanzania, but if these issues are addressed then the country will have a unique opportunity to advance SEA practice as well as to promote environmental management and sustainable development in the region.
Keywords: Q01; Q50; Q51; 330; strategic environmental assessment; policies; plans; and programmes; sustainable development; Tanzania